Dual Specificity Phosphatase 4 Gene Expression in Association with Triple-Negative Breast Cancer Outcome - Baglia, Michelle L (2014)
PURPOSE: Triple-negative breast cancer (TNBC) is an aggressive cancer with limited treatment options. Dual specificity phosphatase 4 (DUSP4) has recently been suggested as a potential marker of chemotherapy resistance for TNBC. METHODS: DUSP4 gene expression levels were measured in breast cancer tissue from 469 TNBC patients aged 20 to 75 years who participated in the Shanghai Breast Cancer Survival Study and their association with recurrence/breast cancer mortality and total mortality was evaluated. Information on breast cancer diagnosis, treatment, and disease progression was collected via medical chart review and multiple in-person follow-up surveys. A Cox regression model was applied in the data analyses. RESULTS: Over a median follow-up of 5.3 years (range: 0.7-8.9 years), 100 deaths and 92 recurrences/breast cancer deaths were documented. Expression levels of transcript variant 1 (NM_001394) and transcript variant 2 (NM_057158) of the DUSP4 gene were studied and were highly correlated (r=0.76). Low DUSP4 expression levels, particularly of variant 1, were associated with both increased recurrence/breast cancer mortality and increased overall mortality. Hazard ratios with adjustment for age at diagnosis and TNM stage associated with below versus above the median expression level were 1.97 (95% confidence interval (CI): 1.27-3.05) for recurrence/breast cancer mortality and 2.09 (95% CI: 1.38-3.17) for overall mortality. Additional adjustment for expression levels of MKI67 and TP53, common treatment types, breast cancer subtype, and grade did not materially alter the observed associations. CONCLUSIONS: Low DUSP4 expression levels predict recurrence and mortality in TNBC patients independently from known clinical and molecular predictors.